2013
DOI: 10.1002/ijc.28437
|View full text |Cite
|
Sign up to set email alerts
|

Comet assay measures of DNA damage are predictive of bladder cancer cell treatment sensitivity in vitro and outcome in vivo

Abstract: Bladder cancer patients suffer significant treatment failure, including high rates of recurrence and poor outcomes for advanced disease. If mechanisms to improve tumour cell treatment sensitivity could be identified and/or if tumour response could be predicted, it should be possible to improve local-control and survival. Previously, we have shown that radiation-induced DNA damage, measured by alkaline Comet assay (ACA), correlates bladder cancer cell radiosensitivity in vitro. In this study we first show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…Mechanisms governing treatment-induced DNA damage are both central to and predictive of bladder cancer cell treatment sensitivity and exemplify a link between DNA damage resistance and both treatment response and tumour aggression [71]. On the other hand, study conducted by Camargo et al , indicated that no relationship was observed between the amount of DNA damage and the level of hMLH1 (a gene involved in the mismatch repair pathway) and RASSF1 (a tumor suppressor gene) in bladder cancer cells treated with cisplatin and gemcitabine.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanisms governing treatment-induced DNA damage are both central to and predictive of bladder cancer cell treatment sensitivity and exemplify a link between DNA damage resistance and both treatment response and tumour aggression [71]. On the other hand, study conducted by Camargo et al , indicated that no relationship was observed between the amount of DNA damage and the level of hMLH1 (a gene involved in the mismatch repair pathway) and RASSF1 (a tumor suppressor gene) in bladder cancer cells treated with cisplatin and gemcitabine.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in bladder cancer, a link has been identified between both DNA damage resistance and tumor aggressiveness in response to treatment [36]. In this study, two of the three patients diagnosed with urinary tract cancer showed a PR and experienced durable disease control for 176 and 387 days.…”
Section: Discussionmentioning
confidence: 88%
“…DNA damage detection from patient samples has been performed for various tumor groups irradiated ex vivo, resulting in robust correlations with radio-responsiveness, as known from clinical behavior [2,5]. Furthermore, monitoring the responses towards damage formation and repair from individual tumors may offer a legitimate chance to monitor cancer treatment and even a possibility to predict clinical response to treatment [6,7]. This is thought to hold true even in spite of the high inter-tumoral and inter-patient heterogeneity that is to be expected from patient samples [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, monitoring the responses towards damage formation and repair from individual tumors may offer a legitimate chance to monitor cancer treatment and even a possibility to predict clinical response to treatment [6,7]. This is thought to hold true even in spite of the high inter-tumoral and inter-patient heterogeneity that is to be expected from patient samples [6,7]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation